Contribution of Kinetic Alfvén Waves to Energetic Electron Precipitation From the Plasma Sheet During a Substorm. Issue 4 (13th April 2023) - Shen, Yangyang; Artemyev, Anton V.; Zhang, Xiao‐Jia; Zou, Ying; Angelopoulos, Vassilis; Vasko, Ivan; Runov, Andrei; Tsai, Ethan; Wilkins, Colin
Abstract: Energetic (≳50 keV) electron precipitation from the magnetosphere to the ionosphere during substorms can be important for magnetosphere‐ionosphere coupling. Using conjugate observations between the THEMIS, ELFIN, and DMSP spacecraft during a substorm, we have analyzed the energetic electron precipitation, the magnetospheric injection, and the associated plasma waves to examine the role of waves in pitch‐angle scattering plasma sheet electrons into the loss cone. During the substorm expansion phase, ELFIN‐A observed 50–300 keV electron precipitation from the plasma sheet that was likely driven by wave‐particle interactions. The identification of the low‐altitude extent of the plasma sheet from ELFIN is aided by DMSP global auroral images. Combining quasi‐linear theory, numerical test particle simulations, and equatorial THEMIS measurements of particles and fields, we have evaluated the relative importance of kinetic Alfvén waves (KAWs) and whistler‐mode waves in driving the observed precipitation. We find that the KAW‐driven bounce‐averaged pitch‐angle diffusion coefficients D α 0 α 0 ${D}_{{α }_{0}{α }_{0}}$ near the edge of the loss cone are ∼10 −6 –10 −5 s −1 for these energetic electrons. The D α 0 α 0 ${D}_{{α }_{0}{α }_{0}}$ due to parallel whistler‐mode waves, observed at THEMIS ∼10‐min after the ELFIN observations, are ∼10 −8 –10 −6 s −1 . Thus, at least in this case, the observed KAWs dominate over the observed whistler‐mode waves in the scattering and precipitation of energetic plasma sheet electrons during the substorm injection. Plain Language Summary: One of the key elements of magnetosphere‐ionosphere coupling is energetic electron precipitation from the magnetosphere to the ionosphere. This precipitation becomes particularly significant and geoeffective during substorms, when it can cause radio transmission interference by increasing ionospheric radio absorption. Understanding the mechanisms of such precipitation is thus critical to space weather nowcasting and forecasting. In this paper, using magnetically conjugate observations between the THEMIS, ELFIN, and DMSP satellites in both the Earth's magnetosphere and ionosphere, and aided with numerical simulations and theoretical estimates, we examine the relative importance of different plasma waves in the scattering and precipitation of energetic electrons from the plasma sheet during a substorm. By comparing the electron scattering efficiencies due to the observed kinetic Alfvén waves (KAWs) and whistler‐mode waves, we conclude that KAWs dominate over whistler‐mode waves, at least in this case, in driving the observed energetic (50–300 keV) electron precipitation by ELFIN during the substorm expansion. Thus, the KAW may be an important, previously overlooked contributor to energetic electron precipitation from the plasma sheet during substorms. Key Points: Conjugate spacecraft observations allow evaluating the relative importance of kinetic Alfvén waves (KAWs) and whistlers in driving energetic electron precipitation KAW‐driven electron bounce‐averaged diffusion rates above 50 keV are one order of magnitude larger than those due to whistler‐mode waves KAWs can contribute to and may dominate the scattering and precipitation of energetic electrons from the substorm plasma sheet